2022
DOI: 10.1097/cm9.0000000000002065
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin as a serum biomarker candidate contributes to the lung fibroblasts activation in chronic obstructive pulmonary disease

Abstract: Background: Fibrosis in the peripheral airways contributes to airflow limitation in patients with chronic obstructive pulmonary disease (COPD). However, the key proteins involved in its development are still poorly understood. Thus, we aimed to identify the differentially expressed proteins (DEPs) between smoker patients with and without COPD and elucidate the molecular mechanisms involved by investigating the effects of the identified biomarker candidate on lung fibroblasts. Methods: The potential DEPs were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Furthermore, Clu supplementation may alleviate hyperoxia-induced lung cell death ( 51 , 52 ). Zhang et al ( 53 ) reported that after Clu silencing, the protein expression levels of a-SMA, collagen I, III and MMP-9 in lung fibroblasts decreased, which inhibited the activation of lung fibroblasts. Besides, inflammatory factors such as IL-6, IL-8 and TNF-α were downregulated in lung fibroblasts to prevent an inflammatory response ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Clu supplementation may alleviate hyperoxia-induced lung cell death ( 51 , 52 ). Zhang et al ( 53 ) reported that after Clu silencing, the protein expression levels of a-SMA, collagen I, III and MMP-9 in lung fibroblasts decreased, which inhibited the activation of lung fibroblasts. Besides, inflammatory factors such as IL-6, IL-8 and TNF-α were downregulated in lung fibroblasts to prevent an inflammatory response ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation was found between Clusterin and FEV1/FVC ratio % in non atopic group. This may be attributed to the inhibiting action of Clusterin in the inflammatory response, differentiation, collagen matrix deposition, and apoptosis of normal human lung fibroblasts (NHLFs) that causes improvement in FEV1/FVC ratio % with Clusterin increase in non atopic group (26). Although Sobeih et al reported that no significant correlations with pulmonary function parameters (FEV1%, FVC% and FEV1/FVC ratio %) in asthmatic patients (18) , Lee et al reported that serum Clusterin levels were increased in severe asthma patients who show lower pulmonary functions tests as it increased with asthma severity (27) .…”
Section: Discussionmentioning
confidence: 99%
“…In consideration of its cellular, immunologic, and metabolic effects, clusterin has associations to various systemic inflammatory, metabolic, and neurological disorders; and their clinical outcome and phenotype, respectively [ 3 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%